2019
DOI: 10.1186/s12864-019-6314-9
|View full text |Cite
|
Sign up to set email alerts
|

Mating precedes selective immune priming which is maintained throughout bumblebee queen diapause

Abstract: BackgroundUnderstanding the mechanisms by which organisms adapt to unfavourable conditions is a fundamental question in ecology and evolutionary biology. One such mechanism is diapause, a period of dormancy typically found in nematodes, fish, crustaceans and insects. This state is a key life-history event characterised by arrested development, suppressed metabolism and increased stress tolerance and allows an organism to avoid prolonged periods of harsh and inhospitable environmental conditions. For some speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 105 publications
(108 reference statements)
1
16
0
Order By: Relevance
“…There is also evidence that mating may also influence the immune system of queens. Molecular evidence has suggested that mating prior to overwintering for B. terrestris resulted in elevated levels of antimicrobial peptides, and these peptide levels were maintained throughout overwintering [112]. Conversely, comparisons between virgin and mating queens have found that mating significantly increases the incidence of melanized spermatheca, which may indicate pathogen transfer during mating [111].…”
Section: Queen Success As a Results Of Matingmentioning
confidence: 99%
“…There is also evidence that mating may also influence the immune system of queens. Molecular evidence has suggested that mating prior to overwintering for B. terrestris resulted in elevated levels of antimicrobial peptides, and these peptide levels were maintained throughout overwintering [112]. Conversely, comparisons between virgin and mating queens have found that mating significantly increases the incidence of melanized spermatheca, which may indicate pathogen transfer during mating [111].…”
Section: Queen Success As a Results Of Matingmentioning
confidence: 99%
“…There have been several studies of the transcriptome and proteome of the different diapause stages of B. terrestris . Comparative analyses indicated that diapause in bumblebees is associated with nutrient storage, core metabolic pathways, stress resistance, insect hormone biosynthesis, and proteins involved in cuticle maintenance [ 37 , 38 , 39 ]. In the current study, comparisons of the protein expression profiles during the three stages of diapause were performed using TMT-labeled proteomics to expand the current understanding of changes at the phosphorylation level.…”
Section: Discussionmentioning
confidence: 99%
“…Key proteins involved in neuroactive ligand–receptor interactions and the glutamatergic synapse pathway related to glutamate neurotransmission were upregulated in early diapause in the female red spider mite ( Tetranychus urticae ) [ 41 ]. The expression levels of glutamate decarboxylase, which plays a role in neurotransmitter synthesis, were increased in the hemolymph of bumblebee queens at 48 h compared to 6 h postdiapause [ 39 ]. In this study, many genes associated with neurotransmitter synthesis were regulated at both the protein and phosphorylation levels during different stages of diapause.…”
Section: Discussionmentioning
confidence: 99%
“…The integrated mRNA and protein level data revealed different levels regulated adult reproductive diapause that occurs in the year-round mass rearing of B. terrestris , and our results suggested that ILPs and JH III played some important roles in the reproductive diapause of queens. Together with results from other related research, , we proposed a model to explain the regulation of reproductive diapause in B. terrestris during the year-round mass rearing process (Figure ). This work could thus facilitate a better understanding of reproductive diapause in the ecologically and economically important pollinators of the world.…”
Section: Discussionmentioning
confidence: 99%